The current standard of Foot and Ankle Fellowship in the UK. Issue 6 (December 2018) - Brown, Rick; Akimau, P.; Hsuan, J.; Williams, T.
Highlights: Detailed definition of the current standard of training in Foot & Ankle Surgery during Fellowship in the UK. Fellows are overall satisfied. Fellows receive a broad experience of different areas of F&A surgery. Fellows are actively involved in Education and under utilised in Research. F&A Surgical Education is the first orthopaedic sub-specialty to review the quality of their Fellowships in an attempt to bring this final essential stage of training up to a uniform standard and then to start to raise that standard. Abstract: Background: The aim of this study was to evaluate the current standards of Fellowship training in Foot and Ankle Surgery Fellowship in the UK. Methods: Thirteen UK post-FRCS (Tr&Orth) or equivalent Fellows completed a questionnaire detailing their outpatient, surgical, teaching and research experience, along with documenting their supervision and terms of employment. Results: A Fellow attended a mean of 2.5 (0.5–4) clinics and 3.84 (2–7) theatre sessions per week. 62% of Fellows had independent clinics. The three largest sub-specialty areas experienced were forefoot surgery, mid or/hindfoot arthritis and deformity correction. 82% of Fellows had a regular MDT meeting. All were involved in both teaching and research, but only 64% had timetabled research sessions. All Fellows were satisfied with their experience and would recommended the Fellowship. Conclusions: The current standard of a post FRCS (Tr&Orth) Fellowship in Foot & Ankle surgery in the UK has been defined. Further improvement will require all Fellows to be involved in a regular MDT meetings, work in an independent clinic, have guaranteed timetabled research time and a ring fenced study leave budget.